2004
DOI: 10.1002/kin.10190
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the catalytic dehydration of HCO3 by zinc(II) complexes of tripod ligands

Abstract: The kinetics of the catalyzed dehydration of HCO 3 − by zinc(II) containing tripod complexes has been studied at 25 • C using the stopped-flow technique. The direction of reaction curve was changed in aqueous solution when the pH of the solution was greater than 7.5. The pH-profile of rates of the dehydration reactions indicates that only the aqua complex catalyzes the dehydration of HCO 3 − via a ligand substitution process. The second-order rate constants for the dehydration of HCO 3 − catalyzed by complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…148 In another study, dehydration of HCO 3 2 by Zn(II) complexes having tripod ligands has been found be catalysed solely by the aqua complex. 149…”
Section: Scheme 13mentioning
confidence: 99%